"Elegant, ferocious, witty": The Professional Glamour of Journalist Barbara Moon (1926–2009). (2nd July 2020) - Couturier, Myriam
Abstract : This paper explores the writing and self-presentation practices of Barbara Moon, a respected journalist and magazine editor who worked in Toronto between the 1950s and 1990s. The entry point into this study was a selection of garments donated by Moon to Toronto's Ryerson Fashion Research Collection in 1997. With a research approach combining material culture, textual, and discourse analyses, connections were drawn between the themes Moon explored in her work, the collection of clothing she chose to archive, and the public commentary around her elegant self-fashioning. Using Moon as a historical case study, this project provides insight into how glamour can be performed, including negotiating gender norms in a male-dominated workplace through fashion and personal appearance.